Local entrepreneurs : motivations, traits and problems. - Koh, Lay Sien. (2013)
Over the last three decades, Singapore has achieved a rate of economic progress equalled by few countries in the world. Singapore has progressed from a poor under-developed country (with a per capita GNP of less than S$1,000 in 1960) to a more advanced developing nation in 1996. Its economic growth is explained by the proliferation of multinational corporations (MNCs) and government-linked companies (GLCs).